Determinan Struktur Modal Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2011-2015 - Fatikhudin, Mochamad (Jurnal Ilmu Manajemen Advantage, 2017)
The purpose of this research is to determine the effect of profitability, liquidity, sales growth, and the firm size in a partial and simultaneous to capital structure in LQ45 company. The population in this study is LQ45 companies listed on the Indonesian Stock Exchange period 2011-2015. This research is use purposive sampling method, and get the total sample of 21 companies. The data used is secondary data derived from Annual Report and Indonesian Capital Market Directory (ICMD). Data analysis that use in this research is multiple regrestion. Result of this research showed profitability has a negative influence to capital structure. Although liquidty profitability where as the variable of liquidity, growth of sales and firm size are not influential to capital structure. Simultatily the profitability, liquidity, growth of sales and firm size are influencial to capital structure. The amount of adjusted R square is 0,239 it means 23,9 percentage dependent variable of capital structure can be explained by four independent variable, they are profitability, liquidity, growth of sales, and firm size, but 76,1 percentage capital structure explained by other variable outside (node).